Tipología de arquitectura vernácula en la amazonía peruana: Un estudio de tres barrios antiguos - García Azan, Marcelo Eduardo; Paima Paredes, Tessy Paola; del Águila Navarro, Jhosep Jarol; Arévalo Lazo, Cinthya (Arquitek, 2024)
Resumen